Growth and Yield Responses of Okra (Abelmoscus Esculentus) Grown on Soil Amended with Dewatered Domestic Sewage Sludge in the West of Cameroon - Fotsa Tiwa, Justine Mireille; Lekeufack, Martin; Tsimi Edzigui, Marcelle Léonce; Fowoung, Diane; Manekeu Tanetsa, Amandine Elodie; Chimi Djiomou, Adrienne; Fonkou, Théophile (European Journal of Applied Sciences, 2024)
Sewage sludge can be good to remedy soil depletion problems by intensive cropping and overcome fertilization costs in agriculture. This study aimed to assess the influence of domestic sewage sludge on the growth and yield of Abelmoschus esculentus in West of Cameroon. Sewage sludge from the digester of sewage treatment plant in University of Dschang was dewatered on filter beds and ground in a mill. It was applied to fields at rates of 10 t/ha (T1), 20 t/ha (T2) and 30 t/ha (T3) to evaluate their effects on the growth and yield of okra (KIRIKOU F1 variety). The experimental design was completely randomized bloc with three replicates. Growth parameters including plant height, leaf number and leaf area and yield parameters including flower buds number, flower number, total fruit number, mature fruit number, fruit diameter and weight were evaluated with time. Growth parameters were collected from the fourth week after sowing at biweekly frequency, while yield parameters were measured weekly from first flower buds formation until end of experiment. The highest plant height, leaf number and leaf area were obtained on the T2 field. Yields in T1, T2 and T3 fields were statistically similar with positive control T4 (0.25 t/ha of 12-14-19 NPK) but differed significantly with the negative control T0 (no fertilizer) which was similar with positive control. The best yield (0.588 t/ha) was achieved from fields fertilized with T2. These results show that sewage sludge, a by-product of domestic sewage treatment, can be used as fertilizer for okra production.